Global Burden of cardiomyopathy and myocarditis in the older adults from 1990 to 2019 - Zhang, Kexin; Cheng, Xuebing; Qu, Na; Song, Hongwei; Luo, Youhong; Ye, Tongtong; Xu, Qian; Tian, Hongzhan; Kan, Chengxia; Hou, Ningning (Frontiers in Public Health, 2022)
Background: Cardiomyopathy and myocarditis (CM-MC) are commonly chronic disease causing heart failure in older adults. We aimed to analyze the burden of CM-MC in older adults aged 60-89 years at the global, regional, and national levels in 204 countries from 1990 to 2019. Methods: Detailed data on CM-MC from 1990 to 2019 were analyzed from the Global Burden of Diseases Study 2019, including incidence, mortality, disability-adjusted life years (DALYs) and the proportion of deaths caused by different risks factors. All results are presented as numbers, age-standardized rates per 100,000 person-years and estimated annual percentage change (EAPC) with an uncertainty interval of 95%. Results: Globally, there were 475,458 (339,942-638,363) incidence cases from CM-MC in 2019; with an age-standardized incidence rate (ASIR) of 16 (13-19.3) per 100,000 person-years. And there were 185,308 (154,610-200,448) deaths, with the age-standardized mortality rate (ASMR) being 4.4 (3.7-4.8). CM-MC resulted in 3,372,716 (2,931,247-3,693,622) DALYs, with an age-standardized DALYs rate (ASDR) of 114.8 (98.7-126.1). Estimated annual percentage change (EAPCs) for ARIS, ARMS, and ARDS has decreased. At the national level, the United States of America had the highest mortality (21,372 [18,924-24,241]) and disability-adjusted life years (407,712 [370,234-470,165]). And China had the highest number of incident (122, 266 [85,925-166,095]). Globally, high systolic blood pressure and alcohol consumption were the top two risk factors for the proportion of CM-MC deaths. Conclusion: CM-MC is still an important cause of early death and chronic disability in older adults. Based on this study, public health agencies should seek more effective methods to prevent and treat CM-MC.